2012
DOI: 10.1016/j.jvs.2011.07.088
|View full text |Cite
|
Sign up to set email alerts
|

Early follow-up and treatment recommendations for isolated calf deep venous thrombosis

Abstract: ICVT can be safely observed in asymptomatic patients without therapeutic anticoagulation. In our study, patients who have had orthopedic procedures, those with malignancy, and those that were immobile seemed to have a higher incidence of clot propagation. In this group, we recommend full anticoagulation until the patient is ambulatory or the follow-up duplex scan is negative. Our data also suggest that a follow-up duplex scan is not beneficial when performed within 72 hours or after 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Ultrasound studies have revealed that in up to 17–33% of all DVT patients the problems originate from calf veins and can cause PE [7,10]. Thus, early diagnosis of isolated calf vein thrombosis is essential, as it may prevent the propagation of thrombosis from calves to thighs and subsequent PE, and decrease the risk of serious long-term complications that are associated with the condition [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound studies have revealed that in up to 17–33% of all DVT patients the problems originate from calf veins and can cause PE [7,10]. Thus, early diagnosis of isolated calf vein thrombosis is essential, as it may prevent the propagation of thrombosis from calves to thighs and subsequent PE, and decrease the risk of serious long-term complications that are associated with the condition [1].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography is the method of choice in patients with suspected DVT due to its noninvasive nature, high sensitivity and specivicity in symptomatic patients, wide availability, portability, and low cost [7]. In contrast to other areas of DVT, the accuracy of US imaging in the detection of calf DVT is highly variable [1].…”
Section: Introductionmentioning
confidence: 99%
“…22 Similarly, a study showed a recanalization rate of 50% for 115 muscular DVT at 4 weeks, 6 and a study on both muscular and axial DVT showed a recanalization rate of 41% within 1e3 months. 10 It has to be noted that guidelines suggest a 12 week treatment for CDVT, 17 and an ultrasound at 12 weeks from CDVT diagnosis was not performed. The recanalization rate may be higher at 12 weeks and in one of the few randomized trials on therapy of symptomatic CDVT, thrombus recanalization at 3 months was seen in 66% of cases in the heparin group and in 60% of cases in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the NRCT included more patients with cancer and immobilization than the RCT (21.4 % vs. 4.7 % and 26.2 % vs. 17.8 %, respectively) [14,15]. Cancer and immobilization have both been found to be signifi cantly associated with a higher risk of proximal progression in patients with isolated distal DVT [13,28]. Cancer is also an important factor, associated with a signifi cantly higher mortality rate after three months of follow-up and a higher VTE recurrence rate after two years of follow-up in patients with isolated distal DVT [29,30].…”
Section: Discussionmentioning
confidence: 99%